The relation between enamel defects in deciduous teeth, nutritional status and the development of basic skills in children with small for gestational age - Miguna, Katina; Soewondo, Williyanti; Oewen, Roosje Rosita; Fadiyana, Eddy (Padjadjaran Journal of Dentistry, 2012)
Introduction:  Small for Gestational Age (SGA)  babies  are those whose birth weight are less than 2 SD or below the 10th percentile curve of Lubchenco intrauterine growth and development. The cause of SGA is due to an Intra-uterine growth restriction (IUGR).  IUGR inhibits the development of various organs, including the enamel of deciduous teeth and the central nervous system (CNS). The research aims to analyzed correlation between enamel defects in deciduous teeth, nutritional status and the development of basic skills in children with SGA. Methods: A total of 28  SGA children aged between 3-6 years were obtained from Hasan Sadikin Hospital. The sample comprised of 20 boys and 8 girls to be studied for tooth enamel defects in deciduous teeth, weight, height and development basic capabilities. Study design was descriptive and analytical, with cross-sectional study. Scoring modification Developmental Defect of Enamel (DDE) of the FDI was used to assess the enamel defects in deciduous teeth. Enamel Defect Score (EDS) was calculated according to the Willyanti’s formula. The nutritional status was measured by measuring height, weight, and age and converted to the diagram of  Body Mass Index (BMI) / Age of the WHO Child Growth Standards. While the development of SGA children basic skills was measured using pre- screening questionnaire development (KPSP). To determine the linkage between enamel defects  in deciduous teeth and nutritional status with basic skills development in SGA children, the non-parametric statistical analysis of Kendall’s Coefficient of Concordance was performed. Results: Statistical test results showed that Kendall’s Coefficient of Concordance (W) = 1.00 is statistically significant with Chi-square value = 56.00 with p (value) <0.01. Conclusion: There is a significant relationship between EDS and nutritional status with the SGA children development of basic skills as well as the development of the child’s ability.